Competitive targeted marketing - Hang-Hyun Jo; Jeong-Yoo Kim (Osaka University, Institute of Social and Economic Research (ISER), 2012)
In this paper, we consider two firms diffusing incompatible technologies and their decision of consumer targeting. The technology adoption is made in two steps. First, once the firms sell their products to their respective targeted consumer, the technology is diffused successively by word-of-mouth communication from the initial consumer to other consumers linked along the network. Then, in the second step, each consumer imitates the technology the neighbors use which fares better, and through this process of imitation, the technology distribution keeps evolving until it reaches the long-run steady state. We demonstrate that the early entrant chooses the minmax location when firms are myopic in the sense that they do not take the imitation possibility into account. If firms consider the possibility of imitation, the best target will tend towards a hub, although the minmax principle in general keeps valid in the sense that it should be the minmax location after considering imitation.
Keywords: 330; Information Diffusion; Technology Adoption; Network Externalities; Compatibility; Learning; Evolution; Targeted Marketing; Marketing; Informationsverbreitung; Technologiewahl; Konsumentenverhalten; Netzwerkökonomik; Lernen; Theorie